Design of Heat Recovery Steam Generator by Recovering Flue Gas from Tin Smelting Processin Pusmet Muntok PT Timah (Persero) Tbk. - Hendi Utomo, Dimas
HRSG (Heat Recovery Steam Generator) is designed to recover flue gas heatfrom tin smelting process at400 °C of temperature and the 14.35 kg/s of mass rate in Pusmet Muntok, PT Timah Tbk. Heat energy from the flue gas is transferred to the feedwater to produce steam at 380 ° C of temperature and 20 barof pressure to generate 900 kW of electricity power. Determination of the material and dimensions of tube, header pipe, and the steam drum is done with reference to the standards of ASME (American Society of Mechanical Engineers) about boiler and pressure vessel. The rate of heat transfer that occurs in economizer, evaporator and superheater can be determined by using the energy balance modeling in Cycle Tempo 5.0. Heat transfer calculations performed to determine the heat transfer rate so close to the results of modeling. Heat transfer calculation is then performed to determine the number of tubes in the economizer, evaporator and superheater. Based on the modeling, the rate of heat transfer that occurs in economizer is at 533.81 kW, evaporator at 2396.99 kW, and superheater at 499.51 kW. Dimensions of tube has 1.25 in. (31.8 mm) of outside diameter, 1.01 in. (25.7 mm) of inside diameter, and 0.12 in. (2.9 mm) of thickness. Dimensions of header pipe have3.5 in. (88.9 mm) of outside diameter, NPS 3, schedule 80, 2.9 in (73.7 mm) of inside diameter, and 0.3 in (7.6 mm) of thickness. Dimensions of the steam drum have26 in. (660 mm) of diameter, 2640 mm of length, and 12 mm of thickness. The material used in the tube, pipe headers, and the steam drum is SA-178 Grade A. Economizer are designed to have the number of tube in every rows 38tubes, 90 tubes in evaporator, and 18 tubesin superheater. Number of tube rows in the economizer, evaporator and superheater is 30 tubes.